Open‐Pore Two‐Dimensional MFI Zeolite Nanosheets for the Fabrication of Hydrocarbon‐Isomer‐Selective Membranes on Porous Polymer Supports. Issue 25 (21st April 2016) - Zhang, Han; Xiao, Qiang; Guo, Xianghai; Li, Najun; Kumar, Prashant; Rangnekar, Neel; Jeon, Mi Young; Al‐Thabaiti, Shaeel; Narasimharao, Katabathini; Basahel, Sulaiman Nasir; Topuz, Berna; Onorato, Frank J.; et al.
Abstract: Two‐dimensional zeolite nanosheets that do not contain any organic structure‐directing agents were prepared from a multilamellar MFI (ML‐MFI) zeolite. ML‐MFI was first exfoliated by melt compounding and then detemplated by treatment with a mixture of H2 SO4 and H2 O2 (piranha solution). The obtained OSDA‐free MFI nanosheets disperse well in water and can be used for coating applications. Deposits made on porous polybenzimidazole (PBI) supports by simple filtration of these suspensions exhibit an n ‐butane/isobutane selectivity of 5.4, with an n ‐butane permeance of 3.5×10 −7 mol m −2 s −1 Pa −1 (ca. 1000 GPU). Abstract : The detemplation and exfoliation of multilamellar MFI nanosheets was achieved by treatment with piranha solution (H2 SO4 /H2 O2 ). A film obtained by directly coating a polymer support with the nanosheets exhibited an n ‐butane/isobutane selectivity of approximately 5.4.